Thyrotropic effects of balneotherapy in Truskavets' spa and their endocrine, vegetative and metabolic accompaniments - Sofiya Ruzhylo; Nataliya Zakalyak; Dariya Popovych; Volodymyr Kikhtan; Teodor Seniv; Oksana Novak; Oksana Mats'ko; Xawery Żukow (Kazimierz Wielki University, 2022)
Background. Previous studies of the Truskavetsian Scientific School of Balneology have studied the effects of course use of bioactive water Naftussya - the main therapeutic factor of the spa - on plasma levels of thyroid hormones in males and females healthy rats and women with thyroid hyperplasia. In men with chronic cholecystitis, the immediate thyrotropic effects of a single use of Naftussya water have been studied. The aim of this study is thyrotropic effects of balneotherapy in Truskavets' spa and their endocrine, vegetative and metabolic accompaniments in men and women with chronic cholecystitis and pyelonephritis. Materials and Methods. The object of clinical-physiological observation were 34 men (23-70 years) and 10 women (39-76 years), who underwent rehabilitation treatment of chronic cholecystitis and pyelonephritis in remission in the Truskavets' spa. The examination was performed twice, before and after a 7-10-day course of balneotherapy. The main object of study was the plasma level of Triiodothyronine. We determined also content in plasma Cortisol, Aldosterone, Testosterone and Calcitonin as well as the parameters of the HRV and metabolism. Results. We find in 16 patients (12 men and 4 women) inhibitory thyrotropic effect, in 22 (16 men and 6 women) neutral, and in 6 men only - enhancing effect of balneotherapy. Each variant of the thyrotropic effect is accompanied by characteristic changes in testosteronemia, calcitoninemia, parathyroid activity, Heart Rate, Baevskiy's Activity Regulatory Systems Index, HRV-markers of vagal tone, Calciemia as well as VLD and LD lipoproteins Cholesterol plasma. Conclusion. Our data confirmed and supplemented the provisions on the multivariate effects of balneotherapy in the spa of Truskavets' on the endocrine and autonomic nervous systems and metabolism of patients.